Detecting the early evidence of real monetary converges for Asean 5 plus three after Asian financial crisis / Maizatul Saadiah Mohamad and Abdul Rahim Ridzuan - Mohamad, Maizatul Saadiah; Ridzuan, Abdul Rahim (2012)
This paper is aiming to investigate the possibilities of monetary convergence in selected Asian countries. The paper evaluates the level of real (represented by GDP) and monetary (represented by CPI and interest rate) converges for the combination for the ASEAN 5+3 countries namely Malaysia, Singapore, Indonesia, Thailand and Philippines as well as Japan, Korea and China. This paper applied various advance time series econometric techniques such as Unit root tests, Johansen Juselius cointegration test to be followed by Vector Error Correction model (VECM) to capture the long run and short run relationship among the variables, Next we used the VECM temporal causality test in order to capture the temporary deviation and generalized variance decomposition is used to determine the leading variables within the system. The outcome suggests a mixed evidence of cointegration between the GDP, CPI and interest rate for the ASEAN 5+3 economies. The integration process may take longer than expected due to the lack of political commitment, economic stability and unpredictable natural disasters. In order to form the economic cointegration, ASEAN 5+3 has to revamp its current financial systems as well as to formulate reasonable and workable economic integration guidelines by setting a clear, consistent and simplified trade procedure and regulation.